Comparative Study of Effectiveness of Oral Acyclovir with Oral Erythromycin in the Treatment of Pityriasis Rosea - Amatya, A; Rajouria, EA; Karn, DK (Kathmandu University Medical Journal, 2012)
Background Pityriasis rosea is an acute, self-limiting disease, probably infective in origin, affecting mainly children and young adults, characterized by distinctive skin eruptions and minimal constitutional symptoms. Both oral Erythromycin and oral Acyclovir have been used in its management. Objectives To compare the effectiveness of oral Erythromycin and oral Acyclovir in the treatment of Pityriasis rosea. Method Forty two patients with clinical diagnosis of Pityriasis rosea were enrolled. They were randomized into two groups. One group was given high-dose oral Acyclovir and another group oral Erythromycin in standard dose. The participants were evaluated one, two, four, six and eight weeks and six months after commencement of the study. Results Forty two patients including 26 males and 16 females completed the study. After 8th week, all patients showed complete response in both the groups. The response to oral Acyclovir compared with that to oral Erythromycin was better and was statistically significant in 1st, 2nd, 4th and 6th weeks. Conclusion Although it is a self-limiting disease which resolves within three weeks to three months, this study reveals that both oral Acyclovir and oral Erythromycin are helpful in decreasing the severity and duration of Pityriasis rosea. Moreover, the study also indicates that oral Acyclovir is more effective than oral Erythromycin in reducing the severity and duration of Pityriasis rosea. KATHMANDU UNIVERSITY MEDICAL JOURNAL  VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 57-61 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6916